As elites políticas de Maringá : um estudo sobre a Câmara Municipal, 1997-2012 - Amaral, Tiago Valenciano Previatto (2011)
This research seeks to answer the question: the city councillors of Maringá, 11th to 14th Legislatures are part of the local political elite. The analysis will be made from the relationship between the "Theory of the Elites" and the profile of lawmakers who were in office during such legislatures. A bibliographic review will be carried out first in order to elucidate the main authors and formulations about the "Theory of the Elites", for a second time, exposing the use of positional method. For the analysis of these profiles, we intend to investigate the recruitment patterns of the city councillors in question: family origin, social background and occupational, educational attainment, political career and political ties, then to analyze the profile of the political elite legislative of Maringá.